Microsatellite markers for the Pilosella alpicola group (Hieraciinae, Asteraceae) and their cross‐amplification in other Hieraciinae genera1. (17th August 2015) - Vít, Petr; Šingliarová, Barbora; Zozomová‐Lihová, Judita; Marhold, Karol; Krak, Karol
Abstract : Premise of the study: Microsatellite markers were developed for the Pilosella alpicola group (Asteraceae), comprising four closely related species distributed in subalpine areas of Europe. These species are believed to have diverged recently, but display contrasting cytogeographic patterns and variation in breeding systems, representing a promising model system for studying plant speciation, adaptation, and recent polyploidization. Methods and Results: We developed 17 microsatellite markers for the P. alpicola group using 454 sequencing. Sixteen markers were polymorphic, with the number of alleles per locus ranging from seven to 16 and observed and expected heterozygosity ranging from 0.45 to 0.84 and 0.72 to 0.92, respectively. Ten and five loci amplified in the related species, P. echioides and P. officinarum, respectively, but only two in Andryala and one in Hieracium s. str. Conclusions: The developed microsatellite markers have high potential to become useful tools to study microevolutionary processes in the P. alpicola group and related Pilosella species.